2019
DOI: 10.1007/s10826-019-01501-w
|View full text |Cite
|
Sign up to set email alerts
|

Questions of Identity in Children Born of War—Embarking on a Search for the Unknown Soldier Father

Abstract: Objectives Children Born of War (CBOW) are important but largely uninvestigated populations. As a result of being fathered by a foreign soldier and born to a local mother, these children often struggle with identity issues and search for their absent fathers their whole lives. Despite CBOW being a part of every society, which has been involved in armed conflicts, there is almost no systematic research about them. Methods We provided a systematic insight into issues of identity that many CBOW face throughout th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
2
13
0
4
Order By: Relevance
“…Moreover, the experiences of stigma not only caused difficulties in constructing coherent and positive identity narratives but also resulted out of PKFC's difficulties to manage their multiple identities aspects. This echoes the experiences of CBOW in other settings [23,24,26].…”
Section: Contributionssupporting
confidence: 78%
See 2 more Smart Citations
“…Moreover, the experiences of stigma not only caused difficulties in constructing coherent and positive identity narratives but also resulted out of PKFC's difficulties to manage their multiple identities aspects. This echoes the experiences of CBOW in other settings [23,24,26].…”
Section: Contributionssupporting
confidence: 78%
“…A conceptual framework defining the psychosocial consequences of growing up as a CBOW was developed in 2012 [ 22 ]. Glaesmer et al emphasize three aspects affecting the mental health of CBOW: experiences of stigmatization and discrimination [ 23 , 24 ], child maltreatment [ 25 ], and identity formation [ 26 ]. While all three categories pose substantial challenges to CBOW [ 27 , 28 ], this article focuses on stigmatization because it was the major concern of those interviewed in the present study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No proof of existence. The vast majority of mothers and other family members remained silent about the biological father and asking questions about him was oftentimes an unspoken taboo irrespective of the background of their parents' relationship (Mitreuter et al, 2019). This conspiracy of silence has been reported as a widespread and omnipresent phenomenon in the context of CBOW (Ericsson and Ellingsen, 2005;Øland, 2005;Schmitz-Köster, 2005;Mochmann and Larsen, 2008;Stelzl-Marx, 2015;Koegeler-Abdi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Identity issues are a widely reported problem amongst CBOW (e.g., Glaesmer et al, 2012) and at the same time remain a largely unresolved and diffuse topic. There has been some recent quantitative and descriptive research (Stelzl-Marx, 2015;Mitreuter et al, 2019) as well as reports from testimonies (Øland, 2005;Schmitz-Köster, 2005) that showed that almost all CBOW set out on an often impossible search for their biological fathers after they had been told the truth about their biological origin. Locating their fathers implied for many to feel more complete and at peace with themselves (Mitreuter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%